You'll grow out of it - Klein, Jessi, 1975- (Grand Central Publishing, 2016)
"YOU'LL GROW OUT OF IT hilariously, and candidly, explores the journey of the twenty-first century woman. As both a tomboy and a late bloomer, comedian Jessi Klein grew up feeling more like an outsider than a participant in the rites of modern femininity. In YOU'LL GROW OUT OF IT, Klein offers-through an incisive collection of real-life stories-a relentlessly funny yet poignant take on a variety of topics she has experienced along her strange journey to womanhood and beyond. These include her "transformation from Pippi Longstocking-esque tomboy to are-you-a-lesbian-or-what tom man," attempting to find watchable porn, and identifying the difference between being called "ma'am" and "miss" ("Miss sounds like you weigh ninety-nine pounds"). Raw, relatable, and consistently hilarious, YOU'LL GROW OUT OF IT is a one-of-a-kind book by a singular and irresistible comic voice"--